Introduction to Soil Solarization - Robert McSorley; Harsimran K. Gill (EDIS)
ENY062, a 6-page illustrated fact sheet by Robert McSorley and Harsimran K. Gill, describes this practice of covering soil surface with plastic to harness the sun’s heat to manage soil weeds, nematodes, diseases, and insects in soil. The authors answer frequently asked questions and outline steps for conducting soil solarization. Includes references. Published by the UF Department of Entomology and Nematology, June 2010.